Characterizing peer roles in an overdose crisis: Preferences for peer workers in overdose response programs in emergency shelters. (1st September 2018) - Bardwell, Geoff; Kerr, Thomas; Boyd, Jade; McNeil, Ryan
Highlights: Novel overdose response interventions are needed in emergency shelters. Peer-led overdose response programs offer a variety of benefits. Relationships with peer workers were built on a shared lived experience. Informal peer support roles optimized overdose response efforts. Abstract: Objectives: A growing body of research points to increasing peer involvement in programs for people who use drugs, although this work has focused primarily on naloxone education and distribution. This study extends this work by examining the roles of peers in leading a novel overdose response program within emergency shelters. Methods: Semi-structured qualitative interviews were conducted with 24 people who use drugs, recruited from two emergency shelters, as well as ethnographic observation in these settings. Interviews were transcribed and analyzed thematically with attention to peer roles. Results: Four themes emerged from the data. First, participants discussed the development of peer support through relationship building and trust. Second, participants described a level of safety using drugs in front of peer workers due to their shared lived experience. Third, peer workers were described as favorable compared to non-peer staff because of nominal power dynamics and past negative experiences with non-peer staff. Last, given the context of the overdose crisis, peer worker roles were often routinized informally across the social networks of residents, which fostered a collective obligation to respond to overdoses. Conclusions: Findings indicate that participants regarded peer workers as providing a range of unique benefits. They emphasized the critical role of both social networks and informal roles in optimizing overdose responses. The scaling up of peer programming in distinct risk environments such as emergency shelters through both formal and informal roles has potential to help improve overdose prevention efforts, including in settings not well served by conventional public health programming.